TO THE PROBLEM OF DIAGNOSTICS OF PROFESSIONAL RESPONSIBILITY OF PERSONNEL - Gofman, O.O.; Vodopyanova, N.E.; Nikiforov, G.S. (Modern Psychology, 2019)
The problem of professional responsibility of the subjects of labor is in the conditions of instability of the modern world and business. The number of employees engaged in various fields of activity (including flexible, virtual organizations) is increasing. The analysis of the existing methods and the sub-scale of the responsibility assessment showed their limitations for use in the selection and development of workers; The article discusses the diagnostic complex, which includes a coordinate system with two variables: 1) the type of organizational culture; 2) the type of professional responsibility. Types of organizational culture at the first approximation are divided into structural and hierarchical (supporting the objective position of the employee, performing discipline) and subject-resource (focused on the subject position of the employee and the ability to creatively solve professional tasks). Professional responsibility is considered systematically and includes the personal (objective, executive or subject managerial position of the employee), cultural (pursuit of individual goals in the organization or team), active (problem solving "here and now" or considering strategic probabilities) components.
Keywords: professional responsibility, organizational culture, diagnostics.